THE MANAGEMENT FUNCTIONS ARE THE RIBS OF SUCCESSFUL ENTREPRENEURSHIP: A STUDY ON ENTREPRENEURS IN BANGLADESH - Uddin, Md. Mayeen (Bangladesh Journal of Multidisciplinary Scientific Research, 2023)
A growing number of people, particularly young people, and women, are establishing their own businesses or starting new ventures, resulting in an increase in entrepreneurship in recent years. Within the first 15 years, 75% of new businesses fail. In Bangladesh, very few studies have been conducted on the utilization and roles of management functions in entrepreneurship. This study sought to highlight the protective qualities of management functions in entrepreneurship in Bangladesh by investigating some factors that define management functions and entrepreneurship success. The descriptive statistics design was used in the study. This study was based on a field survey conducted in the Bangladeshi city of Chattogram and an online questionnaire distributed to entrepreneurs from various sectors in Bangladesh. The sample was chosen using the Cluster Random sampling technique. The questionnaire was given to 207 people, and 150 responded; hence analyzed and presented in frequency distribution tables with percentages and some statistical analysis. Other data were obtained from published academic journals, articles, and other relevant internet materials. The findings indicate that utilizing management functions protects and maintains the success of entrepreneurship. According to the study, entrepreneurs should learn more about and utilize management functions to protect themselves from business failure. JEL Classification Codes: G32, H12, M12, M13, O32.